A quasi-dimensional SI combustion model: a bi-fractal approach. (September 2017) - Daniela, Tufano
Abstract: The main topic of the paper is a detailed description of an extended version of the fractal combustion model (labelled as bi-fractal ) applied for spark ignition (SI) engines, embedded in the commercial software GT-Power as a "user routine". Firstly, a sensitivity analysis has been carried out, with the aim to define a tuning procedure. Subsequently, the combustion model has been calibrated with reference to experimental data of a small-sized two-cylinder SI engine and compared with the traditional version of the fractal approach. Finally, the predictive capability of the bi-fractal approach is assessed over to the whole operating plane, denoting a good agreement for the tested range in terms of both performance and main combustion events.